The politics of the Palestinian Authority : from Oslo to al-Aqsa - Parsons, Nigel Craig, 1966- (New York : Routledge, 2005)
This book is about the development of the PLO from a liberation movement to the Palestinian National Authority. It provides an up-to-date account of the situation in the Middle East, from the Palestinian political perspective.
Conceptualising Palestinian institutions: structure, agency, and transition -- From PLO to PA and on toward statehood: Palestinian institutional development from 1964 to 2003 -- Authoritative leadership and the new national project: the politics of Palestinian diplomacy in Madrid, Washington, and Oslo -- PLO-Israel agreements of the Oslo process -- The bureaucracy and security apparatus of the national project -- Socio-political foundations: civil society, the legislative council, and Fatah as party of state -- Oslo implodes -- After Arafat, on to al-Asqua: Palestinian institutions face the future.
Includes bibliographical references (pages 343-411) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah.; Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah; Palestinian Arabs -- Politics and government -- 1993-; Arab-Israeli conflict -- 1993-; Palestinian National Authority; Palestine question (1948-); Palestiniens -- Politique et gouvernement -- 1993-; Conflit israélo-arabe -- 1993-; HISTORY -- General; Arab-Israeli conflict; Palestinian Arabs -- Politics and government; Middle East -- Palestinian National Authority; Since 1993